2021
DOI: 10.3390/agronomy11091687
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrogen Fertilization and Fungicide Application at Heading on the Gluten Protein Composition and Rheological Quality of Wheat

Abstract: Optimizing the bread-making quality properties of flour is currently one of the main aims of the bakery industry. Therefore, this study has investigated the effects of N fertilization and fungicide application at wheat heading on the protein content (GPC), gluten composition and rheological properties of wheat. Field experiments were carried out in North-West Italy over a 3 year period, on a high protein cultivar of soft winter wheat. Grain samples were collected for each agronomic treatment at four ripening t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
0
7
0
1
Order By: Relevance
“…Grain yield, protein, wet gluten, and starch were increased after the application of N-fertilizer (Table ). N supply has been shown to correlate with tillers, protein concentration, gluten strength and most protein components, total glutenin, gliadin, and the content of most monomeric and polymeric proteins. In contrast, fertilizer-K had less impact on yield . However, K improved the wheat quality by increasing the protein content, wet gluten, and starch content (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Grain yield, protein, wet gluten, and starch were increased after the application of N-fertilizer (Table ). N supply has been shown to correlate with tillers, protein concentration, gluten strength and most protein components, total glutenin, gliadin, and the content of most monomeric and polymeric proteins. In contrast, fertilizer-K had less impact on yield . However, K improved the wheat quality by increasing the protein content, wet gluten, and starch content (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…In wheat production, fertilization and watering strategies are also often considered for quality improvement ( Li et al, 2018 , 2019b ; Yu et al, 2018a , 2021 ). As nitrogen (N) is one of the most important and essential elements for wheat, N fertilizer is usually the most efficient input for simultaneously increasing grain protein content and grain yield in wheat production ( Zebarth et al, 2007 ; Malik et al, 2013 ; Zhen et al, 2018 , 2020 ; Zhong et al, 2018 , 2020 ; Ding et al, 2020 ; Xia et al, 2020 ; Hermans et al, 2021 ; Landolfi et al, 2021 ; Lyu et al, 2021 ; Dong et al, 2022 ; Liu et al, 2022 ; Ma et al, 2022 ). Kichey et al (2007) demonstrated that 50–95% of nitrogen in mature grains is derived from the remobilization of nitrogen stored in the tissues before anthesis.…”
Section: Manipulation Of Fertilization and Watering Regimesmentioning
confidence: 99%
“…The proportions of total gliadins and glutenins including all types were higher at grain maturity with the N240 level compared to N180 (Zhen et al, 2020). Landolfi, D'Auria, et al (2021) studied the effect of N fertilization rate (N80, 80 kg N/ha and N160, 160 kg N/ha, applied as top dressings split equally at tillering and stem elongation) on the gluten protein composition of one old and one modern wheat variety. Higher N supply resulted in an increase of grain protein content from 17.1% to 18.2% for the landrace and from 14.5% to 15.2% for the modern variety.…”
Section: Factors Affecting the Quantity Of Wheat Gluten Proteinsmentioning
confidence: 99%
“…The concomitant application of fungicide at heading caused a slight reduction in grain protein content (−0.3%), but again, gluten composition remained unaffected. In contrast, the environmental conditions during each of the three years had the largest effect on gluten protein composition (Landolfi, Visioli, et al, 2021).…”
Section: Factors Affecting the Quantity Of Wheat Gluten Proteinsmentioning
confidence: 99%